Unexplained early onset epileptic encephalopathy: Exome screening and phenotype expansion. (9th December 2015) - Allen, Nicholas M.; Conroy, Judith; Shahwan, Amre; Lynch, Bryan; Correa, Raony G.; Pena, Sergio D. J.; McCreary, Dara; Magalhães, Tiago R.; Ennis, Sean; Lynch, Sally A.; King, Mary D.
Summary: Early onset epileptic encephalopathies (EOEEs) represent a significant diagnostic challenge. Newer genomic approaches have begun to elucidate an increasing number of responsible single genes as well as emerging diagnostic strategies. In this single‐center study, we aimed to investigate a cohort of children with unexplained EOEE. We performed whole‐exome sequencing (WES), targeting a list of 137 epilepsy‐associated genes on 50 children with unexplained EOEE. We characterized all phenotypes in detail and classified children according to known electroclinical syndromes where possible. Infants with previous genetic diagnoses, causative brain malformations, or inborn errors of metabolism were excluded. We identified disease‐causing variants in 11 children (22%) in the following genes: STXBP1 (n = 3), KCNB1 (n = 2), KCNT1, SCN1A, SCN2A, GRIN2A, DNM1, and KCNA2 . We also identified two further variants (in GRIA3 and CPA6 ) in two children requiring further investigation. Eleven variants were de novo, and in one paternal testing was not possible. Phenotypes were broadened for some variants identified. This study demonstrates that WES is a clinically useful screening tool for previously investigated unexplained EOEE and allows for reanalysis of data as new genes are being discovered. Detailed phenotyping allows for expansion of specific gene disorders leading to epileptic encephalopathy and emerging sub‐phenotypes.